Advising a cardiac disease gene positive yet phenotype negative or borderline abnormal athlete: Is sporting disqualification really necessary?. (24th October 2012) - Richard, Pascale; Denjoy, Isabelle; Fressart, Véronique; Wilson, Mathew G.; Carré, François; Charron, Philippe
Abstract : The sudden cardiac death (SCD) of an athlete is a rare and tragic event, often caused by a number of inherited heart muscle disorders, namely the cardiomyopathies and primary arrhythmia syndromes (also known as cardiac ion channelopathies). Recent advances in the understanding of the molecular genetics of these heritable cardiovascular diseases present new challenges for clinicians who manage athletes with these types of heart muscle conditions. Unfortunately, the clinical heterogeneity of many of these SCD diseases are also matched by the genotypic heterogeneity associated with the pathogenesis of the disease. A particularly challenging situation arises when the sports physician and attending cardiologist are presented with an athlete who demonstrates a familial context of inherited cardiac disease or presents mild cardiac abnormalities suggestive of inherited cardiac disease. Alongside the complete cardiac evaluation, genetic testing may be proposed as an additional diagnostic tool in this clinical conundrum. However, debate still remains on how extensive the screening should be, in particular the use and interpretation of genetic testing in that setting. The aim of this review is to examine the role of genetic testing within the diagnostic algorithm of preparticipation screening of athletes. This will be achieved by providing the sports medicine physician with simple current cardiac genetic knowledge for the main inherited cardiac conditions known to cause SCD. Furthermore, it will examine current knowledge for the role of genetic testing upon the prediction of SCD, concluding with its impact on the sport eligibility and disqualification conundrum using case examples from our genetic testing laboratory.